Place of Geography in School Level Curriculum - Shrestha, Suman Kumar (The Third Pole: Journal of Geography Education, 2021)
This paper examines the place of geography in the school- level curriculum in Nepal. The rearm curriculum defines as the totality of student experiences that occur in the educational process. Specifically, it is referred to a planned sequence of instruction, or a view of the student'; experiences in terms of the educator; or school's; instructional goals. After the establishment of Durbar High School in Nepal in 1910 and the School Leaving Certificate Board in 1990, the subject of Geography was formally introduced. This subject had recognized as a compulsory subject at the school level curriculum before the NESP. After the NESP (1971), the issue had allocated 50 marks, becoming has becomes an optional subject since 1982. Geographic concepts have been taught after the introduction of the social studies curriculum at the secondary level since 1992.At present, geography is teaching in Nepal as an elective subject from secondary level to higher education. However, this subject seems less of a priority for students than mathematics, computer, and account. For this purpose, data collected from the review of the report published from the Education Commissions, Curriculum Development Center, the records of the National Examination Board, e-resources, and other concerned bodies. This paper concludes that geography subject at the school level is in a crisis. However, with the inclusion of geographic information systems (GIS) and spatial planning in the curriculum from the school level, the future of this subject looks bright.